Epidemiological Study of Various Malignancies in Rajasthan: A Comprehensive Analysis - Rohit Gangawat,; Lavina Bagoria,; Shweta Ratanpal,; Ritu Kamal Yadav, (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: Cancer epidemiology systematically studies risk factors, incidence, and prevention strategies using data-driven methods. Accurate cancer surveillance and registration are vital for effective control. Still, in developing countries, challenges like limited healthcare access, poor data infrastructure, and lack of trained personnel hinder proper reporting and analysis. Data Source: The investigators searched multiple databases (e.g., PubMed, Google Scholar, Web of Science) focused on cancer in Rajasthan, India, or globally. Out of 150 sources screened, 99 articles, books, and government reports met the inclusion criteria and were selected for final analysis. Summary: According to the available literature, Cancer epidemiology in Rajasthan highlights oral cavity, breast, cervix, lung, brain and prostate cancers as the most common types, with oral and lung cancers predominant among males due to high tobacco use. Breast and cervical cancers are leading concerns for women, often linked to late diagnosis and poor awareness, especially in rural areas. Conclusion: Rajasthan requires urgent attention to strengthening cancer surveillance, promoting public awareness, and encouraging region-specific research, as these are essential to improving health outcomes and ensuring equitable healthcare planning and policy-making.